Effectiveness of Siwaslih Application Implementation in Monitoring the 2024 Bantul Regency Election - Niflah Mutiara Maulida Putri; Dian Eka Rahmawati (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
This study analyzes the effectiveness of the Siwaslih Application in supervising the 2024 local election in Bantul Regency. Siwaslih is a digital innovation developed by the Election Supervisory Agency (Bawaslu) to enhance transparency, data accuracy, and the speed of supervisory reporting. The research employs a descriptive qualitative approach, collecting primary data through interviews with commissioners, sub-district supervisors, village supervisors, polling station supervisors, and operators in Bambanglipuro and Banguntapan Districts, as well as secondary data from official documents and Bawaslu reports. The findings indicate that Siwaslih is relatively effective in supporting election supervision by enabling real-time reporting from polling stations, accelerating communication, reducing manual workloads, and improving transparency. Its effectiveness is reflected in supervisory efficiency at scale, the accuracy of hierarchical reporting, and the ease of use of a smartphone-based application. However, the study also identifies challenges related to limited digital literacy, uneven internet connectivity, and technical shortcomings, including documentation quality and the absence of offline features. Overall, the Siwaslih Application is effective but requires further feature development and capacity building to optimize digital election supervision.